A Web Base E-Waste Management and Data Security System - GODFREY OISE (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
With the introduction and expansion of ICT, there has been an increase in e-waste and the safety of information in e-waste. An empirical study was conducted in Benin City using a well-designed questionnaire distributed among university college students in higher education, telecommunication providers, civil servants, computer dealers, computer technicians, and e-waste collectors to suggest a framework for e-waste management and an information security tool. An average of four hundred respondents have been surveyed. The data were analyzed using SPSS, and the findings show that the human eye is inadequate for e-waste management and information security tools. The findings also revealed a well-known horrible way of thinking closer to the safety of statistics in damaged systems, owing primarily to a lack of information and the inconveniences associated with it. To address this, a framework and a functional online net website have been improved, which are based on reputation and sensitization of e-waste management and information security. This tool has been suggested as a proper e-waste management and information security tool.